Workforce Analysis of the Australian Rail Transport Industry (ARTI) - Mahendran, Anusha (Center for Research in Applied Economics, 2009)
Despite a slowing in economic activity both internationally and nationally, the Australian rail transport industry (ARTI) is still reporting the existence of skill shortages amongst specified professions. This paper explores this interesting phenomenon more closely by analysing the ARTI workforce and providing a contemporary profile of its major employment trends and characteristics, using the most recently released ABS Census data. Like other industries the ARTI experienced substantial rationalisation of its workforce during the 1990's which resulted in considerable downsizing of employee numbers, reduced intake of young recruits and a significant decrease in training investment and skills development. The combined effect has left the ARTI facing several personnel problems including widespread labour shortfalls, an aging workforce and difficulties in relation to staff attraction and retention. The ARTI's heavy reliance on the skills of its personnel therefore means that such labour issues are likely to have important implications for the industry's prospective output capacity.